Peer Relationship and Self-Confidence of Junior High School Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
The study aimed to determine the status of peer relationships and level of self-confidence of junior high school students at Union Christian College (UCC) San Fernando City, La Union, for the academic year 2022-2023 as the foundation for a suggested homeroom guidance. The study involved one hundred sixty-seven (167) junior high school students as respondents. The descriptive-correlational research technique was used in this study; an adapted peer relationship and self-confidence questionnaire checklist was used in data collection; and data were managed using descriptive and inferential statistics.The researchers found that the majority of the respondents have close relationships with their peers. Additionally, they have a high level of self-confidence. However, there is a need for further revitalization of these areas as they do not meet the optimal levels. Furthermore, there is a significant relationship between the junior high school students' peer relationship status and their level of self-confidence, which implies that better levels of peer relationship increases their level of self-confidence, and vice versa. The researchers propose homeroom guidance that can help students strengthen and boost their peer relationships and self-confidence. Furthermore, a similar study can be conducted to validate the results revealed in this study and include other factors not within the scope of this investigation.
Keywords: peer relationship; self-confidence; homeroom guidance